2005
DOI: 10.1093/jpepsy/jsi063
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Cognitive-Behavioral Family Intervention for Pediatric Recurrent Abdominal Pain

Abstract: These results, in combination with previous studies, add support to the effectiveness of CBT intervention in reducing the sensory aspects of RAP. Results are discussed with respect to the cost-benefit of integrated medical and short-term psychological services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
173
0
11

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 229 publications
(188 citation statements)
references
References 28 publications
4
173
0
11
Order By: Relevance
“…However, CBT resulted in similar decreases in complaints as in earlier studies that did find a difference between CBT and control. 8,12 In the study by Levy et al, 8 parents reported a similar decrease in disability, whereas the trial by Robins et al 12 showed an equivalent child-reported reduction of disability directly after treatment and at 6-and 12-month follow-up. Moreover, the 60% success rate suggests that the CBT protocol investigated in this study is indeed an effective treatment of pediatric FAP.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…However, CBT resulted in similar decreases in complaints as in earlier studies that did find a difference between CBT and control. 8,12 In the study by Levy et al, 8 parents reported a similar decrease in disability, whereas the trial by Robins et al 12 showed an equivalent child-reported reduction of disability directly after treatment and at 6-and 12-month follow-up. Moreover, the 60% success rate suggests that the CBT protocol investigated in this study is indeed an effective treatment of pediatric FAP.…”
Section: Discussionmentioning
confidence: 91%
“…The most likely explanation for the equal effectiveness of CBT and IMC in the current study lies in the more active nature of the IMC control condition used for this study as opposed to control conditions used in other studies. 8,12 We purposefully designed the control condition to be this active to ensure children in both interventions received equal amounts of attention from their therapist/doctor and would have equal opportunities to build a supportive relationship with their therapist/doctor. After all, it is well known in both the medical and psychological literatures that these nonspecific treatment factors may account for a considerable part of treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used frequently in the functional assessment of pediatric pain, including both acute pain (Gidron et al, 1995;Barnum et al, 1998) and chronic pain such as headaches (e.g., Palermo and Kiska, 2005), fibromyalgia (e.g., Kashikar-Zuck et al, 2002), complex regional pain syndrome (e.g., Eccleston et al, 2004), juvenile rheumatoid arthritis (e.g., Reid et al, 2005), sickle cell disease (e.g., Peterson and Palermo, 2004), recurrent abdominal pain (e.g., Robins et al, 2002;Walker et al, 2005), irritable bowel syndrome (e.g., Claar et al, 1999), and inflammatory bowel disease (e.g., Tojek et al, 2002). The FDI also has served as an outcome measure in treatment intervention studies for pain patients, including a randomized clinical trial of behavioral treatment for abdominal pain (e.g., Robins et al, 2005), an evaluation of cognitive behavioral treatment for chronic pain , and an open-label trial of citalopram for treatment of recurrent abdominal pain (Campo et al, 2004).…”
Section: Introductionmentioning
confidence: 99%